The global move into the zero interest rate and high debt trap - Gunther Schnabl (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2013)
The paper identifies based on the monetary overinvestment (malinvestment) theories by Wicksell (1898), Mises (1912) and Hayek (1929) monetary policy mistakes in large industrial countries issuing international currencies. It its argued that a benign neglect towards monetary policy reform in a world dominated by financial markets has led to a erosion of the allocation and signaling function of the interest rate, which has triggered an excessive rise of government debt and structural distortions in the world economy. The backlash of high government debt levels on monetary policy making is argued to lead to the hysteresis of low interest rates and high government debt levels. In this context, monetary reform is discussed with respect to the exit from low interest rates and high debt policies and a reform of the prevalent world monetary system. It is concluded that enhanced competition between dollar and euro as international currencies, which is refereed by East Asia, can be a promising approach towards a more stable world monetary system.
Keywords: E42; E58; F33; F44; 330; Economic Instability; Credit Cycles; Monetary Policy; Hayek; Mises; Monetary Policy Reform; Currency Competition